The subjective concept of morbidity: its assessment and connection with the motivation for treatment in persons who underwent psychosis - N. B. Lutova; M. Y. Sorokin; O. V. Makarevich; V. D. Wied (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
Medication compliance and motivation for treatment, as adaptive- compensatory reactions of patients to the awareness of the fact of their own ill- being, are based on subjective perception of the disorder. To date, there is a shortage of objective methods for assessing the subjective concept of morbidity in psychotic patients.160 inpatients with psychosis in anamnesis were examined: nosologically according ICD-10 80%—F2, 11%—F3, 9%—F0. A self-questionnaire was adapted to the Russian language for determining the subjective meaning and significance of psychosis (Susi). The results of its internal and external (when compared with data on the severity of productive and negative symptoms, subjective assessment of the severity of the condition and treatment motivation of patients) validation are presented.Conclusions. The applicability of the concept of subjective morbidity in patients with mental disorders is shown. The role of the subjective attitude to the disease in case of its perception as a destructive life event is associated in patients with a violation of the structure of motivation for treatment. On the contrary, the ability of patients to form a subjective meaning of the disease can be considered as a guarantee of more intense therapeutic motivation.